Integrasi Prinsip Syariah dalam Fungsi Intermediasi Lembaga Keuangan Syariah - Dewi Sukma Kristianti (Undang: Jurnal Hukum, 2020)
As a financial intermediary institution, Sharia Financial Institutions (LKS) have the responsibility to carry out their business activities by complying with sharia principles, which in the Indonesian context are stated in a number of Fatwas from the National Sharia Council-Indonesian Ulema Council (DSN-MUI). This article discusses why compliance with sharia principles has so far been a problem in LKS business activities, even though the presence of LKS in Indonesia has been nearly a quarter of a century. In this article it is shown that the legal substance of the principles of sharia, as stated in a number of DSN-MUI Fatwas, is still general in nature, so it is not operational and leads to inappropriate interpretations. As a result, the intermediation function of LKS is equated with the intermediation function of conventional financial institutions, and Islamic financing is also equated with credit or receivables. Apart from the fact that the provisions in the DSN-MUI Fatwa are still abstract, another factor that causes the practice not to comply with sharia principles is the weakness of the supervisory element in the LKS, namely the sharia supervisory board (DPS), which is placed parallel to the board of directors, making supervision difficult to be effective. Moreover, DPS membership turned out to be possible to be concurrently in several LKS, so that the supervisory function was not focused and was potentially biased. In the future, it is hoped that the fatwa will contain more operational content and institutional supervision must be made effective and focused. Abstrak Sebagai lembaga intermediasi keuangan, Lembaga Keuangan Syariah (LKS) memiliki tanggung jawab untuk melaksanakan kegiatan usahanya dengan memenuhi prinsip syariah, yang dalam konteks Indonesia sebagaimana tercantum dalam sejumlah Fatwa Dewan Syariah Nasional-Majelis Ulama Indonesia (DSN-MUI). Artikel ini membahas mengapa kepatuhan prinsip-prinsip syariah sejauh ini masih menjadi persoalan dalam kegiatan usaha LKS, padahal kehadiran LKS di Indonesia sudah hampir seperempat abad lebih. Dalam artikel ini ditunjukkan, substansi hukum tentang prinsip-pinsip syariah, sebagaimana yang tercantum dalam sejumlah Fatwa DSN-MUI, masih bersifat umum, sehingga tidak operasional dan menimbulkan interpretasi yang tidak tepat. Akibatnya, fungsi intermediasi LKS disamakan dengan fungsi intermediasi Iembaga keuangan konvensional, dan pembiayaan syariah disamakan pula dengan kredit atau utang piutang. Selain ketentuan dalam Fatwa DSN-MUI yang masih abstrak, faktor lain yang menyebabkan ketidakpatuhan pada prinsip syariah adalah lemahnya unsur pengawas dalam LKS, yaitu dewan pengawas syariah (DPS), yang ditempatkan sejajar dengan direksi, sehingga pengawasan menjadi sulit efektif. Terlebih lagi keanggotaan DPS ternyata dimungkinkan untuk dirangkap dalam beberapa LKS, sehingga fungsi pengawasan tidak terfokus dan potensial bias. Ke depan diharapkan fatwa berisi materi muatan yang lebih operasional, dan kelembagaan pengawasan juga mesti dibuat efektif dan terfokus.